Dividend policy and share price volatility evidence from listed non-financial firms in sri lanka - Kengatharan, L.; Jeyan Suganya, D.F. (University of Jaffna, 2021)
The prime objective of this research is to investigate the impact of dividend policy on share price volatility in Colombo Stock Exchange (CSE). A sample of 81 listed non -financial firms from CSE in Sri Lanka is examined using panel data analysis for a five years period from 2013 to 2017. Dividend policy of the firms has been measured by dividend pay-out, dividend yield and dividend per share and which are explanatory variables of the study after controlling for firm size and financial leverage. According to the random effect regression analysis, only 25% of the movements in share prices are explained by the explanatory variables considered in this study. Dividend yield shows significant positive impact on share price volatility whereas dividend per share shows the significant negative impact on share price movements. Firm size illustrates significant negative influence on share price volatility by indicating large size of companies share price volatility is high. But, dividend pay-out and financial leverage are not significantly persuaded on share price volatility in this study. Therefore, it is concluded that dividend yield, dividend per share and firm size have significant impact on price volatility in Sri Lankan context and findings of the study are in line with the dividend relevance theory. Dividend policy can be considered as the protective mechanism to maintain share price volatility in order to enhance the shareholders wealth.
Keywords: Dividend payout; Dividend yield; Dividend per share; Share price volatility